Oochoristica pseudocotylea (Cestoda, Skrjabinochoridae) — новый вид в фауне СССР - Шарпило, В.П.; Радченко, Н.М.; Корнюшин, В.В. (Вестник зоологии, 1983)
An illustrated redescription of a cestode, Oochoristica pseudocotylea. for the first time found in Eumeces lizard in the USSR territory.